Lavender and Chamomile Aromatherapy Effectivity on Sleep Quality in the Third Trimester Pregnant Women - Mahmujianah Mahmujianah; Elfira Sri Futriani; Farida Murtiani; Aninda Dinar Widiantari (Universitas Wijaya Kusuma Surabaya, 2023)
One of the commonest issues found in pregnant women, mainly in the third trimester, was sleep disruption. Decreasing sleeping time could be a cause of increasing anxiety and/or physical discomfort as higher gestational age. This affected physical and emotional condition such as decreasing concentration, tiredness, and emotional imbalance. The Purpose of this study was to examine lavender and chamomile aromatherapy effectivity on sleep quality of the third semester pregnant women in Semper Barat I Primary Health Care. This study was a quasi-experimental study. Participants were 30 pregnant women which would be divided into two groups interventions, randomly. the participants asked to fill Pittsburgh sleep quality index (PSQI) questionnaire before and after intervention. Three drops of essential oil mixed with water was used to fill diffuser. It will be put in the bedroom for two weeks. Lavender and chamomile aromatherapy were effective to improve sleep quality in our participants. Average score of PQSI after intervention using lavender aromatherapy was dropped significantly (11,3 vs 5,73; p=0,0001) as well as chamomile aromatherapy (10,53 vs 6,53; p=0,0001). These facts could be used to help pregnant women to improve sleep quality. It is suggested to healthcare worker to use nonpharmacological therapy as well as this technique.